Antibacterial Activity of Ethyl Acetate Fraction of Centella asiatica by Soxhletation Extraction Against Pseudomonas aeruginosa - Anggraeni, Baiq Annisa Ulfi; Mukhlishah, Neneng Rachmalia Izzatul; Rosyunita, Rosyunita (Jurnal Biologi Tropis, 2024)
Treatment of P. aeruginosa infection often involves antibiotics but these bacteria can develop resistance. An alternative strategy is developing drugs from natural ingredients such as gotu kola herb (Centella asiatica) which contains potential antibacterial secondary metabolites. This study aims to test the antibacterial activity of the ethyl acetate fraction of C. asiatica extracted by the soxhletation method against clinical isolates of P. aeruginosa and identify the secondary metabolites. The research used laboratory experiment using the disc diffusion method (Kirby-Bauer) in vitro. It includes 3 treatment groups with concentrations of 5.000 ppm, 7.500 ppm, and 10.000 ppm and 2 control groups: positive (colistin) and negative (DMSO 10%). The diameter of the inhibition zone served as an indicator of activity, and each group was reproduced five times. The biggest inhibitory zone diameter, with an average of 3 mm, was formed by the C. asiatica ethyl acetate fraction at a concentration of 7.500 ppm, according to the results. Secondary metabolites such triterpenoids, flavonoids, and phenolics were detected by phytochemical analyses. The ethyl acetate fraction of C. asiatica exhibited antibacterial activity against clinical isolate P. aeruginosa, as demonstrated by the significant difference between all concentration series with the positive control in the Mann-Whitney post-hoc test results.